Sintomas de desatenção e hiperatividade em adolescentes: relações com a prática esportiva, o lazer e relacionamento interpessoal - Rizzo, Maria Fernanda Thomé de (2008)
Attention-Deficit Hyperactivity Disorder (ADHD) presents itself as the main cause that leads children and teenagers looking for mental health ambulatories. It is well known that a lot of individuals that do not fill diagnostics criteria s, presents a lot of symptoms related to hyperactivity and attention deficits and also feel functional failures. Through a random sample of adolescents of low income families localized in the metropolitan region of São Paulo this study investigated the association between the Attention-Deficit Hyperactivity Symptom (ADHS) and the human relations difficulties, their relation with sportive practices and leisure time. The ADHS sample was analyzed with and without mental health problems (MHP). The following instruments were used for this evaluation: Strengths and Difficulties Questionnaire, Brief Impairment Scale and the Questionnaire about Brazilian Economic Classification Criteria. The main results obtained pointed out that these adolescents with ADHS have socialization difficulties with their parents, teachers and colleagues beyond unsatisfactory school performance. The result of this research turn possible to detect aspects about the relation between these teenagers with ADHS and some MHP involved. Additionally appointed the importance and benefits that the motor intervention and the sportive practice since their infancy can bring to these teenagers life s with ADHS, helping them in their socialization and leisure time.